Positive electrode for lithium-sulfur battery containing different conductive materials and lithium secondary battery containing the same

JP2025505190AActive Publication Date: 2025-02-21LG ENERGY SOLUTION LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024546322
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-24
Filing Date
2023-03-24
Publication Date
2025-02-21
Estimated Expiration
2043-03-24

AI Technical Summary

Benefits of technology

【0023】 リチウム-硫黄二次電池において、本発明による新規な導電材の組合せを含むことで電池の出力特性が改善され、容量が高くなる効果を奏する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025505190000001_ABST
    Figure 2025505190000001_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode for a lithium-sulfur battery, the positive electrode comprising a sulfur-carbon composite containing a porous carbon material and sulfur (S) as a positive electrode active material, a first conductive material having a fibrous shape with an average particle size of 5 μm or less, and a second conductive material containing secondary particles formed by agglomeration of two or more CNT primary particles. The novel combination of conductive materials according to the present invention improves the output characteristics of the battery and increases the capacity.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lithium-sulfur battery having improved battery performance, such as output and capacity.

[0002] This application claims priority to Korean Patent Application No. 10-2022-0036689, filed on March 24, 2022, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]

[0003] The positive electrode of a lithium-sulfur battery contains a conductive material in the range of 0 to 10 wt% based on 100 wt% of the positive electrode material to ensure electronic conductivity. Typically, activated carbon materials such as carbon black, denka black, and ketjen black, carbon fibers, or carbon nanotubes (CNTs) are used as the conductive material.

[0004] When using CNTs or carbon fibers, they are usually pre-dispersed so that the fiber strands are completely dispersed, or they can be used as powder particles with entangled carbon fibers. However, no technology has yet been proposed to optimize the performance improvement of conductive materials by controlling such a dispersion state. Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention aims to provide a novel combination of conductive material components and contents that can improve output and capacity characteristics in a positive electrode for a lithium-sulfur battery. Another objective of the present invention is to provide a positive electrode for a lithium-sulfur battery including the novel combination of conductive materials, and a lithium secondary battery including the positive electrode. [Means for solving the problem]

[0006] A first aspect of the present invention relates to a positive electrode material composition for a lithium-sulfur battery, the composition comprising a positive electrode active material, a conductive material, and a binder material, the positive electrode active material comprising a sulfur-carbon composite comprising a porous carbon material and sulfur (S), the conductive material comprising a first conductive material and a second conductive material, the first conductive material being fibrous with an average particle size of 5 μm or less, the second conductive material comprising secondary particles formed by agglomeration of two or more CNT primary particles, the second conductive material having an average particle size of 10 μm to 70 μm, The positive electrode active material, conductive material, and binder material are contained in the ranges of 80 wt % to 97 wt %, 2 wt % to 10 wt %, and 2 wt % to 10 wt %, respectively.

[0007] According to a second aspect of the present invention, in the first aspect, the first conductive material includes CNTs, and the CNTs have an average number of layers of 1 to 20.

[0008] In a third aspect of the present invention, in the second aspect, the first conductive material includes CNTs, and is included in an amount of 0.1% to 0.5% relative to 100 wt% of the total weight of the positive electrode active material, the binder material, and the conductive material.

[0009] According to a fourth aspect of the present invention, in any one of the first to third aspects, the first conductive material includes carbon fibers, and the carbon fibers have a diameter of 100 nm to 2 μm.

[0010] According to a fifth aspect of the present invention, in any one of the first to fourth aspects, the CNTs that are the second conductive material have an average number of walls of 1 to 20, and an average diameter of the CNT primary particles is 0.4 nm to 100 nm.

[0011] According to a sixth aspect of the present invention, in any one of the first to fifth aspects, the positive electrode active material contains 0.1 wt% to 5 wt% of a first conductive material and 1 wt% to 5 wt% of a second conductive material with respect to a total weight of 100 wt% of the positive electrode active material, the binder material and the conductive material.

[0012] According to a seventh aspect of the present invention, in any one of the first to sixth aspects, the porous carbon material has a BET specific surface area of ​​a primary particle of 100 m 2 / g~3,000m 2 / g.

[0013] According to an eighth aspect of the present invention, in any one of the first to seventh aspects, the porous carbon material includes one or more selected from the group consisting of activated carbon, carbon nanotubes (CNTs), and graphene.

[0014] According to a ninth aspect of the present invention, in any one of the first to eighth aspects, the CNTs have an average number of walls of 1 to 20.

[0015] According to a tenth aspect of the present invention, in any one of the first to ninth aspects, the positive electrode active material contains 70 wt % or more of a sulfur-carbon composite with respect to 100 wt % of the positive electrode active material.

[0016] According to an eleventh aspect of the present invention, in any one of the first to tenth aspects, the sulfur-carbon composite contains 70 wt % or more of sulfur with respect to 100 wt % of the sulfur-carbon composite.

[0017] According to a twelfth aspect of the present invention, in any one of the first to eleventh aspects, the sulfur-carbon composite has at least one of a state in which sulfur and a carbon material are simply mixed to form a composite, a state in which the composite has a core-shell structure, and a state in which internal pores of a carbon material are filled with sulfur.

[0018] A thirteenth aspect of the present invention relates to a positive electrode for an electrochemical device, the positive electrode comprising the positive electrode material composition according to any one of the first to twelfth aspects.

[0019] A fourteenth aspect of the present invention relates to a lithium secondary battery including the positive electrode for an electrochemical device.

[0020] The present invention also relates to a method for producing a positive electrode forming slurry, the method comprising the steps of: mixing the positive electrode material composition according to any one of the first to twelfth aspects with a second solvent; adding a first conductive material adjusted to have an average particle size of 5 μm or less; adding a second conductive material in a powder form, the second conductive material including secondary particles formed by agglomeration of two or more CNT primary particles, the second conductive material including the secondary particles having an average particle size of 10 μm to 70 μm.

[0021] According to a sixteenth aspect of the present invention, in the fifteenth aspect, the second solvent includes one or more selected from water and an organic solvent.

[0022] According to a seventeenth aspect of the present invention, in the fifteenth or sixteenth aspect, when the first conductive material contains CNTs, the CNTs are mixed with a first solvent and introduced into the slurry in the form of a mixed solution. Effect of the Invention

[0023] In a lithium-sulfur secondary battery, by including the novel conductive material combination according to the present invention, the output characteristics of the battery are improved, and the capacity is increased. [Brief description of the drawings]

[0024] [Figure 1] 1 shows the output and capacity characteristics of the batteries according to Examples 1 and 2 of the present invention. [Diagram 2] The measurement results of the specific resistance of the electrodes according to Comparative Examples 1, 3, and 4 are shown. [Diagram 3] The measurement results of the specific resistance of the electrodes according to Comparative Examples 1, 6, 7, and 8 are shown. [Figure 4a] 4 shows the measurement results of the discharge characteristics of the batteries according to Comparative Examples 1 to 4. [Figure 4b] 4 shows the measurement results of the discharge characteristics of the batteries according to Comparative Examples 1 to 4. [Diagram 5] The measurement results of the discharge characteristics of the batteries according to Comparative Examples 1, 5 and 6 are shown. [Figure 6] The measurement results of the discharge characteristics of the batteries according to Comparative Examples 1, 9, and 10 are shown. [Figure 7] 1 shows the discharge characteristics of the batteries according to Example 1 and Comparative Examples 1 and 11. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] Hereinafter, a preferred embodiment of the present invention will be described in detail with reference to the attached drawings. Prior to this, the terms and words used in the specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as having meanings and concepts according to the technical ideas of the present invention, in accordance with the principle that the inventor himself can appropriately define the concepts of terms in order to best describe the invention.

[0026] Throughout the specification, when a part "comprises" a certain element, it does not mean excluding other elements, but means that the part may further include other elements, unless otherwise specified.

[0027] The terms "about," "substantially," and the like, used throughout this specification, when given the meaning inherent in the manufacturing and material tolerances, are used to mean a numerical value or a approximation thereof, and are used to prevent unconscionable infringers from unfairly using disclosures in which precise or absolute numerical values ​​are recited to aid in the understanding of this application.

[0028] Throughout this specification, the phrase "A and / or B" means "A or B, or all of these."

[0029] In the present invention, the "specific surface area" is measured by the BET method, and specifically, can be calculated from the amount of nitrogen gas adsorbed at liquid nitrogen temperature (77K) using a BELSORP-mini II manufactured by BEL Japan.

[0030] As used herein, the term "polysulfide" refers to a polysulfide ion (S x 2- , x = 8, 6, 4, 2) and Lithium polysulfide (Li 2 S xor LiS x - , x=8, 6, 4, 2) is a concept that includes both.

[0031] The term "composite" as used herein means a material in which two or more materials are combined to form physically and chemically distinct phases, thereby exhibiting a more effective function.

[0032] The term "porosity" as used herein means the ratio of the volume occupied by pores to the total volume of a structure, and is expressed in units of "%". It may be used interchangeably with terms such as void ratio and porosity.

[0033] In the present invention, "particle size D 50 " means the particle size based on 50% of the volume cumulative particle size distribution of the particles. 50 can be measured using the laser diffraction method. For example, particles are dispersed in a dispersion medium, introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), and irradiated with ultrasonic waves of about 28 kHz at an output of 60 W. Then, a volume cumulative particle size distribution graph is obtained, and the size of the particle that accounts for 50% of the volume cumulative amount is calculated.

[0034] In the present invention, the "fiber thickness" refers to the average fiber thickness when a fibrous carbon material is observed under a scanning electron microscope (SEM). When multiple peaks are observed in the particle size distribution measured by a laser diffraction method, the fiber thickness can also be estimated from the particle size at which the smallest peak is located.

[0035] In addition, the size and thickness of each component shown in the drawings are arbitrarily shown for convenience of explanation, and the present invention is not necessarily limited to such illustrations. In the drawings, thicknesses are enlarged to clearly show multiple layers and regions. In the drawings, thicknesses of some layers and regions are exaggerated for convenience of explanation.

[0036] In addition, throughout the specification, when a part "comprises" a certain element, this means that it may further include other elements without excluding other elements, unless otherwise specified.

[0037] The present invention relates to a positive electrode material composition for a lithium-sulfur battery. In one embodiment of the present invention, the positive electrode material composition includes a positive electrode active material, a conductive material, and a binder material. In the positive electrode material composition, the positive electrode active material may be included in an amount of 80 wt% to 97 wt%, the conductive material in an amount of 2 wt% to 10 wt%, and the binder in an amount of 2 wt% to 10 wt%, based on the total weight of the positive electrode active material, the conductive material, and the binder material. Meanwhile, the positive electrode material composition may further include a solvent, if necessary, which may further include at least one of a first solvent and a second solvent, as described below.

[0038] Next, each of the above components will be described in more detail.

[0039] positive electrode active material The positive electrode active material according to the present invention includes a sulfur-carbon composite. Preferably, the positive electrode active material includes 80 wt% or more, preferably 90 wt% or more of the sulfur-carbon composite relative to 100 wt% of the positive electrode active material, and more preferably, the positive electrode active material may be composed of only the sulfur-carbon composite. Also, the sulfur content is preferably 70 wt% or more relative to 100 wt% of the sulfur-carbon composite.

[0040] In one embodiment of the present invention, the sulfur-carbon composite may be a composite of the sulfur and the carbon material simply mixed together, or may be a coating or support having a core-shell structure. The coating form of the core-shell structure is a coating of either the sulfur or the carbon material with the other material, and for example, the surface of the carbon material may be surrounded by sulfur, or vice versa. The support form may be a form in which the inside of the carbon material, particularly the internal pores, are filled with sulfur. The form of the sulfur-carbon composite may be any form that satisfies the content ratio of the sulfur-based compound and the carbon material presented above, and is not limited to the present invention. Meanwhile, in the present invention, the content of sulfur is preferably 70 wt % or more based on the total weight of the positive electrode active material.

[0041] The sulfur alone does not have electrical conductivity, and therefore is used in combination with a carbon material. For the carbon material, see the description below. In one embodiment of the present invention, the sulfur is inorganic sulfur (S 8 ), Li 2 S n (n≧1), disulfide compounds such as 2,5-dimercapto-1,3,4-thiadiazole, 1,3,5-trithiocyanuric acid, etc., organic compounds and carbon-sulfur polymers (C 2 S x ) n , x=2.5 to 50, n≧2). Preferably, inorganic sulfur (S 8 ).

[0042] Lithium-sulfur batteries have been attracting attention as a next-generation secondary battery due to their high discharge capacity and theoretical energy density, as well as the fact that sulfur, which is used as the positive electrode active material, is abundant and inexpensive, which reduces the manufacturing cost of the battery and makes them environmentally friendly.

[0043] In lithium-sulfur batteries, sulfur, the positive electrode active material, is a non-conductor, so to compensate for its low electrical conductivity, a sulfur-carbon composite is usually used, which is a composite of sulfur and a conductive carbon material.

[0044] The sulfur-carbon composite includes a porous carbon material and sulfur. In one embodiment, the sulfur-carbon composite has sulfur supported in pores of the porous carbon material.

[0045] The carbon material has a porous structure including a plurality of pores on the surface and inside, and serves as a support that provides a framework for uniform and stable immobilization of sulfur, and compensates for the low electrical conductivity of sulfur to facilitate electrochemical reactions. In particular, the carbon material that serves as a sulfur support in the sulfur-carbon composite has a wide BET specific surface area and an appropriate particle size D 50 When the catalyst has a certain size, it is possible to increase the amount of sulfur supported, but at the same time, the irreversible capacity is low, and the energy density is increased, thereby increasing the utilization rate of sulfur during an electrochemical reaction.

[0046] In one embodiment of the present invention, the BET specific surface area of ​​the carbon material is at least 100 m 2 / g or more, up to 3,000m 2 In addition, or independently, the carbon material may have a primary particle diameter D 50 can be from 1 μm to 50 μm.

[0047] The BET specific surface area and particle size D of the carbon material 50 When the range is satisfied, sulfur can be uniformly dispersed on the inside and outside surfaces of the carbon material, while the irreversible capacity can be reduced and the electrochemical reactivity of sulfur can be increased. In addition, the use of the carbon material improves the electrochemical reactivity, stability, and electrical conductivity of the sulfur-carbon composite, thereby improving the capacity and life characteristics of the lithium-sulfur battery and showing optimal charge / discharge performance even if sulfur loss or volume change occurs during charge / discharge.

[0048] The particle size D of the primary particles 50If the diameter of the primary particles is more than 50 μm, it is difficult for the lithium ions to move into the particles due to the limitations of mass transport, making it difficult to efficiently use the sulfur located in the center of the carbon. 50 If the particle size is less than 1 μm, it is difficult to increase the solid content because a large amount of solvent is required in the process of producing the electrode slurry, and sufficient pores between the particles are not secured, resulting in a decrease in output.

[0049] In the sulfur-carbon composite of the present invention, the carbon material used as the sulfur support can be generally prepared by carbonizing various carbon precursors.

[0050] Meanwhile, in one embodiment of the present invention, the pores of the carbon material may have a diameter of 0.5 nm to 200 nm based on the longest diameter. The carbon material is not particularly limited as long as it is spherical, rod-like, needle-like, plate-like, tubular or bulk-like and can be generally used in lithium-sulfur batteries.

[0051] The carbon material may be any porous and conductive carbon-based material commonly used in the art, and may include at least one selected from the group consisting of graphite, graphene, carbon black such as denka black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, carbon nanotubes (CNTs) such as single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs), carbon fibers such as graphite nanofibers (GNFs), carbon nanofibers (CNFs), and activated carbon fibers (ACFs), graphite such as natural graphite, artificial graphite, and expanded graphite, carbon nanoribbons, carbon nanobelts, carbon nanorods, and activated carbon.

[0052] In the sulfur-carbon composite according to the present invention, the sulfur is located on at least one of the inside and outside surfaces of the pores of the carbon material, and in this case, it may be present in an area of ​​less than 100%, preferably 1% to 95%, more preferably 60% to 90% of the entire inside and outside surface of the carbon material. When the sulfur is present on the surface of the carbon material within the above range, it can exhibit the maximum effect in terms of the electron transfer area and the wettability of the electrolyte. Specifically, since the sulfur is impregnated thinly and uniformly on the surface of the carbon material in the above range, it is possible to increase the electron transfer contact area during the charge and discharge process. If the sulfur is located in an area of ​​100% of the entire surface of the carbon material, the carbon material is completely covered with sulfur, which reduces the wettability of the electrolyte and the contact with the conductive material contained in the electrode, making it difficult to transfer electrons and unable to participate in the reaction.

[0053] In one embodiment of the present invention, the sulfur-carbon composite can be obtained by the following production method.

[0054] The method for producing the sulfur-carbon composite according to the present invention is not particularly limited and may be a method commonly known in the art, and may be prepared by a composite method including a step of (S1) mixing a carbon material with sulfur and a step of (S2) composite.

[0055] The mixing in step (S1) is for increasing the degree of mixing of sulfur and the carbon material, and may be performed using a stirrer commonly used in the art. In this case, the mixing time and speed may be selectively adjusted according to the content and conditions of the raw materials.

[0056] The compounding method in step (S2) is not particularly limited in the present invention, and may be a method commonly used in the art. For example, a method commonly used in the art, such as dry compounding or wet compounding such as spray coating, may be used. For example, a method may be used in which the mixture of sulfur and carbon material obtained after mixing is heat-treated so that the molten sulfur is uniformly coated on the inside and outside surfaces of the carbon material. Meanwhile, in one embodiment of the present invention, a process of pulverizing the mixture of sulfur and carbon material by a method such as ball mill pulverization is performed before the heat treatment. In one embodiment of the present invention, the heat treatment is performed at a temperature condition of 120° C. to 160° C. for about 20 minutes to 24 hours, and a heating device such as an oven may be used.

[0057] The sulfur-carbon composite prepared by the above-mentioned preparation method has a structure with a high specific surface area, a high sulfur loading, and an improved sulfur utilization rate. This not only improves the electrochemical reactivity of sulfur, but also improves the accessibility and contactability of the electrolyte, thereby improving the capacity and life characteristics of lithium-sulfur batteries.

[0058] Conductive material The positive electrode material composition according to the present invention includes a conductive material, which includes a first conductive material and a second conductive material.

[0059] The first conductive material is fibrous or acicular, and has an average particle size of 5 μm or less according to a PSD (particle size distribution) analysis. The PSD can be measured using a particle size distribution measuring device. For example, the first conductive material can be introduced into a commercially available laser diffraction particle size distribution measuring device (e.g., Microtrac S3500) to measure the difference in diffraction pattern according to particle size when the particles pass through a laser beam, and calculate the particle size distribution.

[0060] In one embodiment of the present invention, the average particle size may be a value determined by dry analysis or wet analysis of PSD analysis. Dry analysis is, for example, a method of analyzing particle size by scattering particles to be analyzed in the air, and wet analysis is a method of analyzing particle size by dispersing particles to be analyzed in a solvent (e.g., water). Meanwhile, the average particle size of the first conductive material may be maintained in the positive electrode material composition, the positive electrode forming slurry, and the positive electrode obtained therefrom.

[0061] The first conductive material may include at least one selected from the group consisting of carbon nanotubes and carbon fibers. In one embodiment of the present invention, the carbon fibers may have a fiber diameter of 100 nm to 2 μm. The carbon nanotubes may have an average number of walls of 1 to 20, and the average diameter (diameter) of the primary particles (one carbon nanotube) of the carbon nanotubes may be 0.4 nm to 100 nm. Here, the diameters of the carbon fibers and primary particles of the carbon nanotubes may be measured using a Transmission Electron Microscope (TEM) or a Scanning Electron Microscope (SEM).

[0062] The average diameter of the primary carbon nanotube particles may be calculated by averaging the diameters of a plurality of primary particles in a carbon nanotube image observed by TEM or SEM, and the number of observed primary particles may be, for example, 10 to 50, but is not limited thereto.

[0063] The carbon fiber diameter of 100 nm to 2 μm may mean that the diameters of a plurality of carbon fibers randomly selected from a carbon fiber image observed by TEM or SEM are in the above range. For example, when an image of a carbon fiber is taken by TEM and 10 to 50 carbon fibers are randomly selected from the image and their diameters are measured, if all of the measured diameters are 100 nm to 2 μm, the carbon fiber diameters may be considered to be 100 nm to 2 μm. However, the number of carbon fibers selected for diameter measurement is not limited to 10 to 50.

[0064] As described above, when the first conductive material contains one or more selected from the group consisting of carbon nanotubes and carbon fibers, a battery containing a positive electrode material composition containing the first conductive material has a low resistivity and can achieve the effect of improving capacity.

[0065] Meanwhile, when the first conductive material contains CNT, the CNT content is preferably in the range of 0.1wt% to 0.5wt% based on the total weight of the positive active material, binder material, and conductive material (100wt%). If the content is below this range, the conductive path connection effect is low and no output improvement effect is observed, and if the content is higher than this range, the CNT forms a film and blocks the pores, preventing smooth battery reaction and reducing the output.

[0066] Meanwhile, when the first conductive material contains carbon fiber, the content of the carbon fiber is preferably in the range of 1 wt% to 10 wt% based on the total weight of the positive active material, binder material, and conductive material (100 wt%). If the content is below this range, the conductive path connection effect is low and no output improvement effect is observed, and if the content is higher than this range, the carbon fiber forms a film and blocks the pores, preventing smooth battery reaction and reducing the output.

[0067] In one embodiment of the present invention, the first conductive material may be dispersed in a first solvent such as water or a suitable organic solvent (NMP, acetone) to maintain an average particle size of 5 μm or less and to enhance dispersibility in the positive electrode material composition, and may be added to the positive electrode material composition in the form of such a mixed solution. In particular, CNTs exist as undispersed secondary particles in a gas-phase synthesis state, and if the degree of dispersion is insufficient even if the CNTs are dispersed, they tend to aggregate and become secondary particles, and may become large particles with an average particle size exceeding 5 μm. Therefore, when the above-mentioned mixed solution is prepared, the average particle size of the CNTs may be controlled to 5 μm or less. On the other hand, when carbon fibers are used as the first conductive material instead of CNTs, the carbon fibers may be sufficiently dispersed during the preparation of the mixed solution (slurry) of the positive electrode composition without being dispersed in a solvent in advance, and may have an average particle size of 5 μm or less. Therefore, the first conductive material does not necessarily have to be added in the form of a mixed solution.

[0068] Meanwhile, in one embodiment of the present invention, the second conductive material has an average particle size of 10 μm to 70 μm according to a PSD measurement result. The second conductive material may include CNT. The CNT may have an average number of layers of 1 to 20, and an average diameter of the primary particles may be 0.4 nm to 100 nm. The second conductive material has an average particle size of 10 μm to 70 μm and includes secondary particles formed by aggregation of two or more primary particles. The second conductive material is added to the positive electrode material composition in a state including secondary particles of the average particle size, and maintains the average particle size even in the positive electrode material composition. Unlike the first conductive material, it is preferable that a process of preparing a mixed solution and pre-dispersing the mixed conductive material before being added to the positive electrode material composition is not applied.

[0069] Meanwhile, in one specific embodiment of the present invention, the first conductive material may be contained in a range of 0.1 wt% to 5 wt% and the second conductive material may be contained in a range of 1 wt% to 5 wt% with respect to a total weight of 100 wt% of the positive electrode active material, binder material, and conductive material.

[0070] Binder Material The binder material serves to improve the adhesion between positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector. Specific examples of the binder material include polyvinyllidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof. One or a mixture of two or more of these may be used.

[0071] Other cathode materials In one embodiment of the present invention, the positive electrode active material may be composed only of the sulfur-carbon composite. Meanwhile, in another embodiment of the present invention, the positive electrode active material may further include, in addition to the sulfur-carbon composite, one or more additives selected from a transition metal element, a Group IIIA element, a Group IVA element, sulfur compounds of these elements, and alloys of these elements with sulfur.

[0072] In a specific embodiment of the present invention, the positive electrode active material layer may further include a lithium transition metal composite oxide represented by the following Chemical Formula 1:

[0073] [Chemical formula 1] Li a Ni b Co c M 1 d M 2 e O 2 In the above formula 1, M 1 is Mn, Al or a combination thereof, and desirably may be Mn or Mn and Al.

[0074] Said M2 is at least one selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta and Nb, preferably at least one selected from the group consisting of Zr, Y, Mg and Ti, more preferably Zr, Y or a combination thereof. 2 Although the elements are not essential, when contained in an appropriate amount, they can play a role in promoting grain growth during firing or improving the stability of the crystal structure.

[0075] Meanwhile, a positive electrode slurry and a positive electrode may be prepared using the positive electrode material composition as follows.

[0076] The positive electrode slurry may be prepared by mixing the positive electrode material composition and a second solvent. The solid content of the positive electrode slurry may be in the range of 20 wt% to 50 wt%. The solid content of the positive electrode slurry does not include the second solvent, and if the first conductive material is pre-dispersed and added in the form of a mixed solution, it means only the remaining components of the pre-dispersed solution excluding the first solvent.

[0077] The first conductive material is adjusted to have an average particle size of 5 μm or less and added to the slurry, while the second conductive material is added in the form of a powder containing CNT secondary particles, the secondary particles having an average particle size of 10 μm to 70 μm.

[0078] In one embodiment of the present invention, the second solvent may include at least one selected from water and an organic solvent (NMP or acetone).

[0079] Meanwhile, as described above, when the first conductive material contains CNTs, the CNTs may be mixed with a first solvent and pre-dispersed to have an average particle size of 5 μm or less, and then added to the slurry in the form of such a mixed solution.

[0080] When the positive electrode slurry is prepared in this manner, it may be applied to at least one surface of a metal thin film for a positive electrode current collector and dried to manufacture a positive electrode. In the manufacture of the positive electrode, specific process contents for adjusting the thickness and porosity by applying the slurry, drying, and pressing may be substituted for known techniques in the technical field to which the present invention pertains.

[0081] For example, a second solvent may be prepared and the above-mentioned positive electrode material composition may be added to prepare a positive electrode slurry. Meanwhile, in one embodiment of the present invention, the binder material of the positive electrode material composition may be first added to the second solvent to prepare a binder solution, and then the remaining materials may be added sequentially. As the second solvent for preparing the positive electrode slurry, it is preferable to use one that can uniformly disperse the positive electrode material composition and is easy to evaporate. Representative examples include acetonitrile, methanol, ethanol, tetrahydrofuran, water, and isopropyl alcohol.

[0082] The slurry thus prepared is applied to a current collector and dried to form a positive electrode. The slurry may be coated on the current collector in an appropriate thickness depending on the viscosity of the slurry and the thickness of the positive electrode to be formed.

[0083] The coating may be performed by a method known in the art. For example, the positive electrode active material slurry may be dispensed on one side of the positive electrode current collector and then uniformly dispersed using a doctor blade, etc. Alternatively, the coating may be performed by a method such as die casting, comma coating, screen printing, etc.

[0084] The drying is not particularly limited, and may be performed within one day at a temperature of 50° C. to 200° C. The drying may be performed using an oven or other device under vacuum conditions.

[0085] Yet another aspect of the present invention relates to a positive electrode including the sulfur-carbon composite. The positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on at least one surface of the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a conductive material, and a binder material. The positive electrode active material layer is derived from the above-mentioned positive electrode material composition, and the specific content of the positive electrode components is substituted for the above-mentioned content. Meanwhile, in one embodiment of the present invention, the positive electrode active material layer may include the above-mentioned positive electrode active material, the conductive material, and the binder material, and may include the positive electrode active material in a ratio of 80 wt% to 97 wt%, the conductive material in a ratio of 2 wt% to 10 wt%, and the binder in a ratio of 2 wt% to 10 wt%, based on the total weight of the positive electrode active material, the conductive material, and the binder material. In addition, the sulfur-carbon composite may be contained in an amount of 70 wt% or more based on the total weight of the positive electrode active material, and the sulfur content of the sulfur-carbon composite may be contained in an amount of 70 wt% or more based on the total weight of the positive electrode active material. In a specific embodiment of the present invention, it is preferable that the sulfur content of the positive electrode active material is contained in an amount of 70 wt% or more based on the total weight of the positive electrode active material.

[0086] Meanwhile, various positive electrode current collectors used in the art may be used as the positive electrode current collector. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. may be used as the positive electrode current collector. The positive electrode current collector usually has a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the positive electrode current collector to increase the adhesive strength of the positive electrode active material. The positive electrode current collector may be used in various forms, such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0087] The present invention also provides a lithium-sulfur battery including an electrolyte and an electrode assembly including a positive electrode containing the sulfur-carbon composite. The electrode assembly includes a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode.

[0088] The electrode assembly may be stacked with a separator interposed between the negative and positive electrodes to form a stack or stack / fold structure, or may be wound up to form a jelly roll structure. When a jelly roll structure is formed, a separator may be further disposed on the outside to prevent contact between the negative and positive electrodes.

[0089] The negative electrode includes a negative electrode current collector and a negative electrode active material layer formed on at least one surface of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material, a conductive material, and a binder.

[0090] Next, the negative electrode will be described in more detail.

[0091] The negative electrode may have a structure in which a negative electrode active material is formed on one or both sides of a long sheet-shaped negative electrode current collector, and the negative electrode active material layer may include a negative electrode active material, a conductive material, and a binder.

[0092] Specifically, the negative electrode may be manufactured by coating one or both sides of a long sheet-shaped negative electrode current collector with a negative electrode slurry prepared by dispersing a negative electrode active material, a conductive material, and a binder in a solvent such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, etc., and then removing the solvent from the negative electrode slurry through a drying process, followed by rolling. Meanwhile, a negative electrode including a non-coated portion may be manufactured by not coating a portion of the negative electrode current collector, for example, one end of the negative electrode current collector, with the negative electrode slurry when coating the negative electrode slurry.

[0093] The negative electrode active material is lithium (Li + The intercalation or deintercalation of lithium ions may include materials capable of reversibly intercalating or deintercalating lithium ions, materials capable of reversibly forming lithium-containing compounds by reacting with lithium ions, lithium metal, lithium alloys, and the like.

[0094] In one embodiment of the present invention, when lithium metal and / or lithium alloy are used as the negative electrode active material for the negative electrode, a metal thin film obtained by thinning these metal materials can be used as the negative electrode, and in this case, it may not include another current collector. The thinned negative electrode may have a thickness of 30 μm to 200 μm. In one embodiment of the present invention, the negative electrode may be one in which a reinforcing material of 100 μm or less is bonded to or inserted into the metal thin film. The reinforcing material may be porous. On the other hand, the reinforcing material may be conductive or non-conductive.

[0095] The substance capable of reversibly inserting or desorbing the lithium ions may be, for example, crystalline carbon, amorphous carbon, or a mixture thereof. Specifically, artificial graphite, natural graphite, graphite carbon fiber, amorphous carbon, soft carbon, hard carbon, etc. may be mentioned, but are not limited thereto. The substance capable of forming a lithium-containing compound reversibly by reacting with the lithium ions may be, for example, tin oxide, titanium nitride, or a silicon-based compound. The lithium alloy may be, for example, an alloy of a metal selected from the group consisting of lithium (Li) and sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn). Desirably, the negative electrode active material is lithium metal, and specifically, it may be in the form of a lithium metal thin film or lithium metal powder. The silicon negative electrode active material may be Si, Si-Me alloy (where Me is one or more selected from the group consisting of Al, Sn, Mg, Cu, Fe, Pb, Zn, Mn, Cr, Ti, and Ni), SiO y (where 0 < y < 2), a Si-C composite, or a combination thereof, and desirably, it may be SiO y (where 0 < y < 2). Since the silicon-based negative electrode active material has a high theoretical capacity, when the silicon-based negative electrode active material is included, the capacity characteristics can be improved.

[0096] The negative electrode current collector may be a negative electrode current collector commonly used in the art. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy may be used. The negative electrode current collector usually has a thickness of 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be provided with fine irregularities to enhance the binding force of the negative electrode active material. For example, the negative electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0097] The conductive material is used to impart conductivity to the negative electrode, and can be used without any particular limitation as long as it has conductivity without inducing a chemical change in the battery to be constructed. Specific examples include graphite such as natural graphite and artificial graphite; carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, carbon nanotube, and other carbon-based materials; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in combination. The conductive material may be usually contained in an amount of 1 wt% to 30 wt%, preferably 1 wt% to 20 wt%, more preferably 1 wt% to 10 wt% based on the total weight of the negative electrode active material layer.

[0098] The binder serves to improve the adhesion between the negative electrode active material particles and the adhesive strength between the negative electrode active material and the negative electrode current collector. Specific examples include polyvinyllidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 1 wt% to 30 wt%, preferably 1 wt% to 20 wt%, more preferably 1 wt% to 10 wt%, based on the total weight of the negative electrode active material layer.

[0099] Meanwhile, the electrode assembly further includes a separator, which is disposed in the electrode assembly in a manner interposed between the negative electrode and the positive electrode. The separator can be any separator that is commonly used as a separator in a lithium secondary battery by separating the negative electrode and the positive electrode and providing a passage for lithium ions to move. Specifically, the separator can be a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof. In addition, a typical porous nonwoven fabric, for example, a nonwoven fabric made of a high melting point glass fiber, a polyethylene terephthalate fiber, or the like, can be used. In addition, a separator coated with a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength.

[0100] In yet another aspect of the present invention, there is provided an electrochemical device including the electrode assembly, the electrochemical device including the electrode assembly and an electrolyte solution housed in a battery case, and the battery case may be of any suitable type, such as a pouch type or a metal can type, that is commonly used in the art, and is not particularly limited thereto.

[0101] As the electrolyte used in the present invention, various electrolytes that can be used in lithium secondary batteries, such as organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes, can be used, and the type is not particularly limited.

[0102] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0103] The organic solvent may be used without any particular limitation as long as it can act as a medium for enabling the movement of ions involved in the electrochemical reaction of the battery. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of solvents that can be used include carbonate solvents such as PC (carbonate); alcohol solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (R is a C2-C20 linear, branched, or cyclic hydrocarbon group that may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolanes.

[0104] Meanwhile, in one embodiment of the present invention, the non-aqueous solvent of the electrolyte preferably contains an ether-based solvent in terms of improving the charge / discharge performance of the battery. Examples of such ether-based solvents include linear ethers (e.g., methoxyethane, ethoxyethane, 1,2-dimethoxyethane, dimethoxymethane, dimethoxyethane), cyclic ethers (e.g., 1,3-dioxolane, tetrahydrofuran, tetrahydropyran, etc.), linear ether compounds (e.g., 1,2-dimethoxyethane, etc.), low-viscosity fluorinated ethers, e.g., 1H,1H,2'H,3H-decafluorodipropyl ether, difluoromethyl 2,2,2-trifluoroethyl ether, 1,2,2,2-tetrafluoroethyl trifluoromethyl ... ether), 1,1,2,3,3,3-Hexafluoropropyl difluoromethyl ether, 1H,1H,2′H,3H-Decafluorodipropyl ether, Pentafluoroethyl 2,2,2-trifluoroethyl ether, and 1H,2H,2′H-Perfluorodipropyl ether, and a mixture of one or more of these may be contained as the non-aqueous solvent.

[0105] The lithium salt may be any compound capable of providing lithium ions used in a lithium secondary battery, without any particular limitation. Specifically, the lithium salt may be LiPF 6 , LiClO 4 , LiAsF 6 , LiBF 4 , LiSbF 6, LiAlO 4 , LiAlCl 4 , LiCF 3 SO 3 , LiC 4 F 9 SO 3 , LiN(C 2 F 5 SO 3 ) 2 , LiN(C 2 F 5 SO 2 ) 2 , LiN(CF 3 SO 2 ) 2 , LiCl, LiI, or LiB(C 2 O 4 ) 2 LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiFSI (lithium bis(fluorosulfonyl)imide), etc. may be used. The concentration of the lithium salt may be within a range of 0.1M to 5.0M, preferably 0.1M to 3.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore excellent electrolyte performance can be exhibited, and lithium ions can be effectively moved.

[0106] In addition to the electrolyte components, the electrolyte may further contain additives for the purpose of improving the life characteristics of the battery, suppressing the capacity reduction of the battery, and improving the discharge capacity of the battery. For example, the additives may be haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, which may be used alone or in combination, but are not limited thereto. The additives may be included in an amount of 0.1 wt% to 10 wt%, preferably 0.1 wt% to 5 wt%, based on the total weight of the electrolyte.

[0107] The shape of the lithium-sulfur battery is not particularly limited, and may be in various shapes such as a cylindrical shape, a stacked shape, a coin shape, and the like.

[0108] The present invention also provides a battery module including the lithium-sulfur battery as a unit cell, which can be used as a power source for medium to large devices that require high temperature stability, long cycle characteristics, and high capacity characteristics.

[0109] Examples of the medium- to large-sized devices include, but are not limited to, power tools powered by electric motors; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and the like; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (Escooters); electric golf carts; and power systems.

[0110] In the following, preferred embodiments of the present invention will be described to aid in understanding the present invention. However, the following embodiments are merely illustrative of the present invention, and it is obvious to those skilled in the art that various modifications and alterations are possible within the scope of the scope and technical ideas of the present invention. Of course, such modifications and alterations are included in the scope of the appended claims.

[0111] Manufacturing Example [Production of sulfur-carbon composite] CNT particles (average number of layers: 6) and sulfur were uniformly mixed and a sulfur-carbon composite was prepared in an oven at 155° C. for 30 minutes. The sulfur content in the sulfur-carbon composite (100 wt%) was 75 wt%.

[0112] [Production of positive electrodes] Example 1 The prepared sulfur-carbon composite, VGCF as a first conductive material, CNT particles (average number of layers: 9) as a second conductive material, and PAA (Polyacrylic acid) as a binder were added to water in a weight ratio of 92.0:2.5:2.5:3.0 to prepare a slurry for preparing a positive electrode. The solid content concentration in the slurry was 25 wt%. The average particle size of the VGCF was 5 μm. The CNT as the second conductive material included aggregates of particles, had an average particle size of 35 μm, and was added to the positive electrode slurry in a powder state. The prepared positive electrode slurry composition was applied to both sides of a 20 μm thick aluminum current collector to a thickness of 250 μm, dried at 50° C. for 12 hours, and pressed with a roll press machine to prepare a positive electrode with a total thickness of 200 μm.

[0113] Example 2 The prepared sulfur-carbon composite, CNT (average number of layers: 2) as a first conductive material, CNT (average number of layers: 9) as a second conductive material, and PAA as a binder were added to water in a weight ratio of 94.3:0.2:2.5:3.0 to prepare a slurry for preparing a positive electrode. The solid content concentration in the slurry was 25 wt%. The CNT as the first conductive material was added to the slurry in a mixed solution state in which it was dispersed in water. In the mixed solution, the ratio of water:CNT:dispersant was 99:0.3:0.7 by weight. The average particle size of the CNT in the mixed solution was 1 μm. The CNT as the second conductive material included aggregates of particles, had an average particle size of 35 μm, and was added to the slurry for the positive electrode in a powder state. The prepared positive electrode slurry composition was applied to both sides of an aluminum current collector having a thickness of 20 μm to a thickness of 250 μm, dried at 50° C. for 12 hours, and pressed with a roll press to prepare a positive electrode having a thickness of 200 μm.

[0114] Comparative Example 1 The prepared sulfur-carbon composite and PAA as a binder were added to water in a weight ratio of 97:3 to prepare a slurry for preparing a positive electrode. The solid content of the slurry was 25 wt%. The prepared positive electrode slurry composition was applied to both sides of an aluminum current collector having a thickness of 20 μm to a thickness of 250 μm, dried at 50° C. for 12 hours, and pressed with a roll press to prepare a positive electrode having a thickness of 200 μm.

[0115] Comparative Example 2 The prepared sulfur-carbon composite, VGCF as a conductive material, and PAA as a binder were added to water in a weight ratio of 94.5:2.5:3.0 to prepare a slurry for preparing a positive electrode. The solid content in the slurry was 25 wt%. The average particle size of the VGCF was 5 μm. The prepared positive electrode slurry composition was applied to both sides of an aluminum current collector having a thickness of 20 μm to a thickness of 250 μm, dried at 50° C. for 12 hours, and pressed with a roll press to prepare a positive electrode having a thickness of 200 μm.

[0116] Comparative Example 3 The prepared sulfur-carbon composite, VGCF as a conductive material, and PAA as a binder were added to water in a weight ratio of 92.0:5.0:3.0 to prepare a slurry for preparing a positive electrode. The solid content in the slurry was 25 wt%. The average particle size of the VGCF was 5 μm. The prepared positive electrode slurry composition was applied to both sides of an aluminum current collector having a thickness of 20 μm to a thickness of 250 μm, dried at 50° C. for 12 hours, and pressed with a roll press to prepare a positive electrode having a thickness of 200 μm.

[0117] Comparative Example 4 The prepared sulfur-carbon composite, VGCF as a conductive material, and PAA as a binder were added to water in a weight ratio of 87.0:10.0:3.0 to prepare a slurry for preparing a positive electrode. The solid content in the slurry was 25 wt%. The average particle size of the VGCF was 5 μm. The prepared positive electrode slurry composition was applied to both sides of an aluminum current collector having a thickness of 20 μm to a thickness of 250 μm, dried at 50° C. for 12 hours, and pressed with a roll press to prepare a positive electrode having a thickness of 200 μm.

[0118] Comparative Example 5 The prepared sulfur-carbon composite, CNT (average number of layers: 2) as a conductive material, and PAA as a binder were added to water in a weight ratio of 96.75:0.25:3.0 to prepare a slurry for preparing a positive electrode. The solid content concentration in the slurry was 25 wt%. The CNT was added to the slurry in the form of a mixed solution dispersed in water. In the mixed solution, the weight ratio of water:CNT:dispersant was 99:0.3:0.7. The average particle size of the CNT in the mixed solution was about 1 μm. The prepared positive electrode slurry composition was applied to a thickness of 350 μm on an aluminum current collector having a thickness of 20 μm, dried at 50° C. for 12 hours, and pressed with a roll press to prepare a positive electrode having a thickness of 200 μm.

[0119] Comparative Example 6 The prepared sulfur-carbon composite, CNT (average number of layers: 2) as a conductive material, and PAA as a binder were added to water in a weight ratio of 96.5:0.5:3.0 to prepare a slurry for preparing a positive electrode. The solid content concentration in the slurry was 25 wt%. The CNT was added to the slurry in the form of a mixed solution in which it was dispersed in water. In the mixed solution, the weight ratio of water:CNT:dispersant was 99:0.3:0.7. The average particle size of the CNT in the mixed solution was about 1 μm. The prepared positive electrode slurry composition was applied to a thickness of 350 μm on an aluminum current collector having a thickness of 20 μm, dried at 50° C. for 12 hours, and pressed with a roll press to prepare a positive electrode having a thickness of 200 μm.

[0120] Comparative Example 7 The prepared sulfur-carbon composite, CNT (average number of layers: 2) as a conductive material, and PAA as a binder were added to water in a weight ratio of 96.0:1.0:3.0 to prepare a slurry for preparing a positive electrode. The solid content concentration in the slurry was 25 wt%. The CNT was added to the slurry in the form of a mixed solution dispersed in water. In the mixed solution, the weight ratio of water:CNT:dispersant was 99:0.3:0.7. The average particle size of the CNT in the mixed solution was about 1 μm. The prepared positive electrode slurry composition was applied to a thickness of 350 μm on an aluminum current collector having a thickness of 20 μm, dried at 50° C. for 12 hours, and pressed with a roll press to prepare a positive electrode having a thickness of 200 μm.

[0121] Comparative Example 8 The prepared sulfur-carbon composite, CNT (average number of layers: 2) as a conductive material, and PAA as a binder were added to water in a weight ratio of 94.0:3.0:3.0 to prepare a slurry for preparing a positive electrode. The solid content concentration in the slurry was 25 wt%. The CNT was added to the slurry in a mixed solution state dispersed in water. In the mixed solution, the weight ratio of water:CNT:dispersant was 99:0.3:0.7. The average particle size of the CNT in the mixed solution was about 1 μm. The prepared positive electrode slurry composition was applied to a thickness of 350 μm on an aluminum current collector having a thickness of 20 μm, dried at 50° C. for 12 hours, and pressed with a roll press to prepare a positive electrode having a thickness of 200 μm.

[0122] Comparative Example 9 The prepared sulfur-carbon composite, CNT (average number of layers: 9) as a conductive material, and PAA as a binder were added to water in a weight ratio of 94.5:2.5:3.0 to prepare a slurry for preparing a positive electrode. The solid content concentration in the slurry was 25 wt%. The CNT contained aggregates of particles, had an average particle size of 35 μm, and was added to the positive electrode slurry in a powder state. The prepared positive electrode slurry composition was applied to both sides of an aluminum current collector having a thickness of 20 μm to a thickness of 250 μm, dried at 50° C. for 12 hours, and pressed with a roll press to prepare a positive electrode having a thickness of 200 μm.

[0123] Comparative Example 10 The prepared sulfur-carbon composite, CNT (average number of layers: 9) as a conductive material, and PAA as a binder were added to water in a weight ratio of 92.0:5.0:3.0 to prepare a slurry for preparing a positive electrode. The solid content concentration in the slurry was 25 wt%. The CNT contained aggregates of particles, had an average particle size of 35 μm, and was added to the positive electrode slurry in a powder state. The prepared positive electrode slurry composition was applied to both sides of an aluminum current collector having a thickness of 20 μm to a thickness of 250 μm, dried at 50° C. for 12 hours, and pressed with a roll press to prepare a positive electrode having a thickness of 200 μm.

[0124] Comparative Example 11 The prepared sulfur-carbon composite, VGCF as a first conductive material, Ketjen black as a second conductive material, and PAA as a binder were added to water in a weight ratio of 92.0:2.5:2.5:3.0 to prepare a slurry for preparing a positive electrode. The solid content concentration in the slurry was 25 wt%. The average particle size of the VGCF was 5 μm. The second conductive material, Ketjen black, contained aggregates of particles, had an average particle size of 35 μm, and was added to the positive electrode slurry in a powder state. The prepared positive electrode slurry composition was applied to both sides of an aluminum current collector with a thickness of 20 μm to a thickness of 250 μm, dried at 50° C. for 12 hours, and pressed with a roll press to prepare a positive electrode with a total thickness of 200 μm.

[0125] [Battery manufacturing] A 35 μm-thick lithium metal thin film was used as the negative electrode together with the positive electrode, and the electrolyte was an organic solvent mixture of 2-methylfuran and dimethoxyethane in a volume ratio of 33:77, with 0.6 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 3 wt% lithium nitrate (LiNO 3 ) and a mixture of these was used.

[0126] Specifically, the prepared positive and negative electrodes were placed facing each other, and a separator made of polyethylene with a thickness of 20 μm and a porosity of 45% was placed between them, and the prepared electrolyte was then injected to prepare a lithium-sulfur battery. The battery was constructed by stacking seven positive and negative electrodes.

[0127] [evaluation] Referring to FIG. 1, when the first and second conductive materials according to the present invention are used as in Examples 1 and 2, it can be seen that the output and capacity at the early and late stages of discharge are all improved.

[0128] Meanwhile, as can be seen from Figures 2 and 3, when only VCGF is used as the conductive material as in Comparative Examples 2 and 3, or when only dispersed CNTs are used as in Comparative Examples 4 and 5, it was confirmed that an improvement effect of lowering the resistivity depending on the amount added was achieved. Therefore, when only VGCF is used at 2.5% as in Comparative Example 2 of Figures 4a and 4b, the output is improved. However, when VGCF is contained at more than 5% and up to 10% as in Comparative Example 4, it can be seen that there is almost no further improvement effect on the output compared to when 5% is used.

[0129] In addition, when dispersed CNTs are used as in Fig. 5, the initial / late output is improved when 0.25% is used as in Comparative Example 5, but the middle / late output is reduced when 0.5% is used as in Comparative Example 6. In addition, when non-dispersed CNT particles are used as in Fig. 6, the effect of improving the capacity and output in the later period is obtained, but there is no effect of improving the initial output.

[0130] On the other hand, as shown in Figure 7, in the case of Comparative Example 1, which does not use CNT, and in the case of Comparative Example 11, which uses Ketjen black as the second conductive material, there is almost no improvement in resistivity and capacity compared to Example 1.

[0131] Experimental Example 1. Method for measuring particle size Using a particle size analyzer (model: Bluewave, manufacturer: Microtrac), the dry method was used. 50 When the carbon material was aggregated into secondary particles, the particle size of the primary particles was observed and measured using a scanning electron microscope (model SEM, manufacturer: JEOL).

[0132] Experimental example 2. Measurement of discharge characteristics The batteries of each Example and Comparative Example were discharged at 0.2 C in CC mode at 25° C. to 1.8 V, and then charged at a constant current of 0.2 C to 2.5 V, and the discharge capacity was measured and compared. The discharge capacity was measured based on the sulfur content (mAh / g(S)).

[0133] Experimental Example 3: Measurement of electrode resistivity The resistivity of the electrode was measured using a Hioki RM2610 device. Specifically, the multi-electrode array of the device was brought into contact with the manufactured electrode, and the resistivity was measured, and the resistivity value of the electrode layer was obtained from the results displayed on the device.

Claims

1. The positive electrode includes a positive electrode active material, a conductive material, and a binder material, The positive electrode active material comprises a sulfur-carbon composite containing a porous carbon material and sulfur (S), the conductive material includes a first conductive material and a second conductive material; the first conductive material is fibrous with an average particle size of 5 μm or less; The second conductive material includes secondary particles formed by agglomeration of two or more CNT primary particles, and the second conductive material has an average particle size of 10 μm to 70 μm; The positive electrode active material, the conductive material and the binder material are contained in the ranges of 80 wt % to 97 wt %, 2 wt % to 10 wt % and 2 wt % to 10 wt %, respectively.

2. 2. The positive electrode material composition according to claim 1, wherein the first conductive material comprises CNTs, and the CNTs have an average number of walls of 1 to 20.

3. 3. The positive electrode material composition according to claim 2, wherein the first conductive material comprises CNTs, and the first conductive material is contained in an amount of 0.1 wt % to 0.5 wt % relative to a total weight of 100 wt % of the positive electrode active material, the binder material, and the conductive material.

4. 2. The cathode material composition of claim 1, wherein the first conductive material comprises carbon fibers, the carbon fibers having a diameter of 100 nm to 2 μm.

5. 2. The positive electrode material composition according to claim 1, wherein the CNTs as the second conductive material have an average number of walls of 1 to 20 and an average diameter of the CNT primary particles of 0.4 nm to 100 nm.

6. 2. The positive electrode material composition of claim 1, comprising 0.1 wt % to 5 wt % of the first conductive material and 1 wt % to 5 wt % of the second conductive material, based on a total weight of 100 wt % of the positive electrode active material, the binder material, and the conductive material.

7. The porous carbon material has a primary particle BET specific surface area of ​​100 m 2 / g to 3,000m 2 The positive electrode material composition according to claim 1 , wherein the positive electrode material composition has a molecular weight of 1.0 to 1.0 g.

8. 2. The positive electrode material composition according to claim 1, wherein the porous carbon material comprises at least one selected from the group consisting of activated carbon, carbon nanotubes (CNTs), and graphene.

9. The positive electrode material composition according to claim 8, wherein the CNTs have an average number of walls of 1 to 20.

10. 2. The positive electrode material composition according to claim 1, comprising 70 wt % or more of the sulfur-carbon composite relative to 100 wt % of the positive electrode active material.

11. The positive electrode material composition according to claim 10, wherein the sulfur content is 70 wt % or more relative to 100 wt % of the sulfur-carbon composite.

12. 2. The cathode material composition according to claim 1, wherein the sulfur-carbon composite has at least one of a state in which sulfur and a carbon material are simply mixed to form a composite, a state in which the composite has a core-shell structure and a state in which internal pores of a carbon material are filled with sulfur.

13. A positive electrode for an electrochemical device comprising the positive electrode material composition according to any one of claims 1 to 12.

14. A lithium secondary battery comprising the positive electrode for an electrochemical element according to claim 13.

15. Mixing the positive electrode material composition according to claim 1 with a second solvent; The first conductive material is added after being adjusted to have an average particle size of 5 μm or less. A method for producing a slurry for forming a positive electrode, wherein a second conductive material is added in a powder form and contains secondary particles formed by agglomeration of two or more CNT primary particles, and the second conductive material containing the secondary particles has an average particle size of 10 μm to 70 μm.

16. The method for producing a slurry for forming a positive electrode according to claim 15, wherein the second solvent includes at least one selected from the group consisting of water and an organic solvent.

17. The method for producing a positive electrode forming slurry according to claim 15, wherein when the first conductive material includes CNTs, the CNTs are mixed with a first solvent and introduced into the slurry in the form of a mixed solution.

Citation Information

Patent Citations

  • Carbon nanotube-sulfur composite containing carbon nanotube aggregates and method for producing the same

    JP2016535716A

  • Positive electrode for lithium ion secondary battery and lithium ion secondary battery

    JP2018097961A

  • Electronic apparatus for processing information for settlement of sold items and method thereof

    KR102395117B1

  • Underwater coating system

    KR102405291B1